High-Throughput Characterization of Viral and Cellular Protein Expression Patterns During JC Polyomavirus Infection - DuShane, Jeanne K.; Wilczek, Michael P.; Crocker, Mason A.; Maginnis, Melissa S. (Frontiers in Microbiology, 2019)
JC polyomavirus (JCPyV) is a ubiquitous human pathogen and the causative agent of a fatal demyelinating disease in severely immunocompromised individuals. Due to the lack of successful pharmacological interventions, the study of JCPyV infection strategies in a rapid and highly-sensitive manner is critical for the characterization of potential antiviral therapeutics. Conventional methodologies for studying viral infectivity often utilize the detection of viral proteins through immunofluorescence microscopy-based techniques. While these methodologies are well established in the field, they require significant time investments and lack a high-throughput modality. Scanning imager-based detection methods like the In-cell Western (ICW), have been previously utilized to overcome these challenges incurred by traditional microscopy-based infectivity assays. This automated technique provides not only rapid detection of viral infection status, but can also be optimized to detect changes in host-cell protein expression during JCPyV challenge. Compared to traditional manual determinations of infectivity through microscopy-based techniques, the ICW provides an expeditious and robust determination of JCPyV infection. The optimization of the ICW for the detection of viral and cellular proteins during JCPyV infection provides significant time and cost savings by diminishing sample preparation time and increasing resource utilization. While the ICW cannot provide single-cell analysis information and is limited in the detection of quantitation of low-expressing proteins, this assay provides a high-throughput system to study JCPyV, previously unavailable to the field. Thus, the high-throughput nature and dynamic experimental range of the ICW can be applied to the study of JCPyV infection.